Violência no espaço escolar : reflexões acerca das estratégias de prevenção aplicadas nas aulas do componente curricular projeto de vida - Félix, Fernanda Seabra (2022)
It is currently perceived how much has been said about education, especially with regard to the new demands that arise in the face of continuous technological innovations, by which society is being subjected. In view of these perspectives, there is a need for behavioral changes in favor of the development of skills that promote in these individuals the ability to become adaptable, flexible, independent and with responsibilities to act as active citizens, participating in the construction of a fair and egalitarian society and not only citizens who move the labor market. To this end, the (BNCC, 2018) proposes a set of skills to be developed in students across the country, among them, the Life Project, with the central objective of making students capable of taking of decisions based on values and principles worked in the school space. Regarding the challenges that are imposed on the ways to prevent school violence, Charlot (2002) and Sposito (2012) corroborate the same assumption that the school institution must present a resignification in its role, that is, enable pedagogical practices that provide new perspectives in order to attribute positive meanings during the development of children and adolescents. However, this research, approved by the Ethics Committee/UFS with CAEE: 51235021.1.0000.5546, is exploratory-descriptive, with a qualitative approach, whose main objective is to promote a reflection on school violence in a perspective of reflecting on prevention/reduction strategies, developed by teachers involved in the Life Project curricular component, in integral high schools in the State of Sergipe, where semistructured interviews and data processing, Discursive Textual Analysis, were used for data collection. with the participation of five teachers from the network who taught the Life Project before as well as during the COVID-19 pandemic. In this way, the results showed us two types of recurrent practices in the school space when referring to the prevention/reduction of violence: actions to mobilize behaviors that aim at good coexistence and tolerance; and interventional actions, where these reveal teaching practices applied by some of the teachers intentionally, of a preventive nature, but punctual and discontinuous. In view of this perspective, it is suggested that prevention practices need to be developed throughout the teaching and learning process, especially in this new curricular component, whose intention is to develop the socio-emotional of their students so that they build interpersonal relationships favorable to their performance both personally and professionally.